(3TQM GdCSHGH hGdYdGeGJ ddSeQbfOis - (3HQgGf GdOjf fajS Hf YhV Hf Mcje GdcQeGfis; (3GdfLjH GdSeQbfOj , eMeO Hf Ydj Hf YeQ GdSeQbfOj, fLjH GdOjf CHh MGeO,J (B619 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd aEf GdYHO GdabjQEdi Gddg fajS Hf YhV GHf Mcje GdWHjH hcGf bSe GdCeQGV GdLRFjI ef gPG Gdaf de jbUO CMO GdCaGVd Edi GdBf dJaSQg hJTQjMg aCQOJ Cf CcTa Ye hLhg ahGFO gPG Gdaf s
(3BNQgG (B:s
(3hCf jbJUQ Ydi eKd LhR GdSQ hQdCHgd , hSGFQ eG jfaY ai VeGO GdaJb , aEfgG JTO GdYVh hJfTa GdQWhHGJ hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3cJH ajg (B: (3JjSjQ GdCSHGH hGdYdGeGJ ai GdWHGFY hGdYdGLGJs
(3hbO cJH GdeJf GdeTQhM HGdMeQIs
(3fSNI KGdKIs
(3hHChdgG JYdjb HGSe GdcJGH jYhO Edi SfI (B1015(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdWHs